2015
DOI: 10.1016/j.febslet.2015.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Strand‐biased gene distribution, purine assymetry and environmental factors influence protein evolution in Bacillus

Abstract: A strong purine asymmetry, along with strand-biased gene distribution and the presence of PolC, prevails in Bacillus and some other members of Firmicutes, Fusobacteria and Tenericutes. The analysis of protein features in 21 Bacillus species of diverse metabolic, virulence and ecological traits revealed that purine asymmetry in conjunction with lineage/niche specific constraints significantly influences protein evolution in Bacillus. All Bacillus species, except for Se-respiring Bacillus selenitireducens, displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Interestingly, genes encoding proteins acting on the lagging strand have evolved at a significantly higher rate than those dealing with the leading strand (13,14). All these features raise the question whether there is a division of labour between the two replicative DNA polymerases, each one being devoted to one strand (21), or if the B. subtilis replisome is more eukaryotic-like in that it relies on a two DNA polymerase system for chromosomal replication (5), using two polymerases at both strands.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, genes encoding proteins acting on the lagging strand have evolved at a significantly higher rate than those dealing with the leading strand (13,14). All these features raise the question whether there is a division of labour between the two replicative DNA polymerases, each one being devoted to one strand (21), or if the B. subtilis replisome is more eukaryotic-like in that it relies on a two DNA polymerase system for chromosomal replication (5), using two polymerases at both strands.…”
Section: Introductionmentioning
confidence: 99%
“…Firmicutes possess three conspicuous genome features: purine asymmetry across the two strands of replication, a marked strand-biased gene distribution ( 5 8 ), and presence of two essential replicative C-family DNA polymerases, PolC and DnaE (also called DnaE3) ( 9 11 ). In contrast, E. coli codes for only one replicative C-family DNA polymerase, the Pol III-α subunit (also termed DnaE1, 11).…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid composition was reported to be correlated with the protein structure classes (Bahar et al, 1997; Horner et al, 2008; Du et al, 2014), the metabolic efficiency (Akashi and Gojobori, 2002; Kaleta et al, 2013), and the translation efficiency (Du et al, 2017). Sueoka (1961, 1962) firstly reported that there is a correlation between GC contents and amino acid composition of proteins, and then the nucleotide bias causes the biased amino acid usage in bacterial and viral genomes was broadly reported (Rooney, 2003; Bohlin et al, 2013; Goswami et al, 2015). Cost-minimization could also shape the amino acid composition (Seligmann, 2003; Raiford et al, 2008; Bivort et al, 2009).…”
Section: Introductionmentioning
confidence: 99%